Coordinated Control Strategy of DC Fault Ride-through for the WF Connected to the Grid Through the MMC-HVDC - Zhu, Bo; Li, Hongying; Xu, Panteng; Jiao, Shi; Zhang, Lin; Xin, Yechun (Frontiers in Energy Research, 2021)
Aiming at the problems of DC fault isolation and power surplus in the HVDC system with large-scale wind farm (WF) integration after single-pole grounding fault, this article designs a modified current transfer modular multilevel converter (M-CT-MMC) topology with DC fault isolation and power dissipation functions. The DC fault current can be isolated through the coordination of each branch of the M-CT-MMC. In terms of surplus power consumption, the control mode switching strategy of the M-CT-MMC is designed to improve the power transmission capability of the non-fault pole and enable it to absorb surplus power independently. Furthermore, a coordinated control strategy of wind turbines and dissipation resistors is designed to absorb surplus power. With the advantages of fast response speed of wind turbines and reliable dissipation resistance, DC fault ride-through under different working conditions is realized. Finally, the effectiveness and feasibility of the coordinated control strategy for DC fault ride-through are verified.